Kajian Perbandingan Idiom Berbasis Tumbuhan dalam Bahasa Indonesia dan Bahasa Mandarin - Lijun Wang; Isah Cahyani; Halimah Halimah; Yulianeta Yulianeta (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study focuses on plant-related idioms, exploring the similarities and differences between the two languages in expressing worldviews and values by comparing the structure, meaning, and cultural context of Indonesian and Chinese idioms. This research uses a descriptive qualitative approach, combining semantic, comparative and cultural analysis to deeply uncover the symbolic meaning of plant idioms and their cultural influences. The results show that Indonesian idioms have diverse forms, are close to life, and embody the cultural qualities of flexibility and inclusiveness, while Chinese idioms are characterized by symmetry and simplicity, highlighting the philosophical tradition of the unity of heaven and man and profound cultural connotations. Moreover, plant idioms, as important carriers of the intermingling of languages and cultures, not only reflect both cultures' unique perspectives on nature and society but also make significant contributions to cross-cultural communication. These idioms also have strategic value in language education, especially in helping to understand and apply cultural symbols more effectively.